Multifunctional self-assembled polymeric nanoprobes for FRET-based ratiometric detection of mitochondrial H2O2 in living cells1. Issue 17 (28th February 2015) - Qiao, Jing; Liu, Zhi; Tian, Ye; Wu, Man; Niu, Zhongwei
<x xml:space="preserve">Abstract</x> A micelle-based and mitochondria-targeting FRET probe was fabricated to ratiometrically detect intracellular mitochondrial H2O2.